Annulatascus nilensis sp. nov., a new freshwater ascomycete from the River Nile, Egypt - M.A. Abdel-Wahab; F.A. Abdel-Aziz; S.S. Mohamed; A.E. Abdel-Aziz (IMA Fungus)
Annulatascus nilensis sp. nov., from freshwater habitats in Egypt, is described, illustrated and compared to other species in the genus. Phylogenetic analyses of its LSU rDNA sequence with similar fungi placed the new species in the genus Annulatascus (Annulatascaceae, Sordariomycetidae incertae sedis). Annulatascus nilensis is characterized by immersed ascomata with an ascomatal neck oriented horizontally to the substrate surface, asci with a long, narrow stalk and massive bipartite apical ring, and 5-11-septate, hyaline ascospores surrounded by a large irregular, granular sheath that is not seen in water.